1998
DOI: 10.1021/ma971227q
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect on the Anionic Equilibrium Polymerization of Six-Membered Cyclic Carbonates

Abstract: Anionic equilibrium polymerization behavior of several six-membered cyclic carbonates was examined. The conversions of the monomers reached a constant below 100%, and the final conversion decreased in the order of 1,3-dioxan-2-one (1) > 5,5-dimethyl-1,3-dioxan-2-one (2) > 5,5-diethyl-1,3-dioxan-2-one (3) ≥ 5-methyl-5-phenyl-1,3-dioxan-2-one (4) > 5-ethyl-5-phenyl-1,3-dioxan-2-one (5). The reactions of 2,2-disubstituted-1,3-propanediols were carried out with phosgene dimer to find that the cyclic carbonate (5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
165
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 34 publications
12
165
0
Order By: Relevance
“…In the absence of compounds to be alkylated, these cyclic carbonates can be broken down to oxiranes and carbon dioxide, which is the reverse of the formation reaction [11]. Aliphatic and aromatic cyclic carbonate can easily be polymerized to a variety of homopolymers and copolymers with high molecular masses [12][13][14][15], [17][18][19][20][21][22]. Openchain carbonic esters can be broken down catalytically at high temperatures to form alcohols, carbon dioxide, and olefins [23].…”
Section: Propertiesmentioning
confidence: 99%
“…In the absence of compounds to be alkylated, these cyclic carbonates can be broken down to oxiranes and carbon dioxide, which is the reverse of the formation reaction [11]. Aliphatic and aromatic cyclic carbonate can easily be polymerized to a variety of homopolymers and copolymers with high molecular masses [12][13][14][15], [17][18][19][20][21][22]. Openchain carbonic esters can be broken down catalytically at high temperatures to form alcohols, carbon dioxide, and olefins [23].…”
Section: Propertiesmentioning
confidence: 99%
“…This polymerization exhibits equilibrium nature, which can be controlled by bulkiness of the substituents. 62 One of the advantages of 6CC is its structural diversity, owing to the utilization of various 1,3-diols as starting materials. For example, 6CC having styrene moiety was easily synthesized (Scheme 20).…”
Section: Application Of Equilibrium Polymerization To Reversible Crosmentioning
confidence: 99%
“…[1][2][3] For their synthesis, various procedures have been used, that is, (i) the polycondensation between the carbonate derivatives and diols, 4 (ii) the ring-opening polymerization of cyclic carbonates, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and (iii) the alternating polymerization of epoxides with carbon dioxide. Among these procedures, the ring-opening polymerizations of cyclic carbonates have the potential to control the molecular weight and to induce copolymerization with other cyclic monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Six-membered cycles (or larger) using anionic initiators tend to polymerize smoothly, yielding the corresponding polycarbonate at a lower temperature (o100 1C). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In contrast, the anionic ring-opening polymerization of the fivemembered ring is thermodynamically unfavorable and proceeds at a higher temperature (4150 1C), causing the elimination of carbon dioxide to produce a copolymer that consists of both carbonate and ether linkages. [20][21][22][23][24][25] However, we reported that the anionic ringopening polymerization of a five-membered cyclic carbonate (MBCG) (Figure 1) possessing the a,D-glucopyranoside structure proceeded even at 0 1C to produce an aliphatic polycarbonate without the elimination of carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%